Assessment of factors affecting intention to leave of employees at Japanese companies in Vietnam : Luận văn ThS. Kinh doanh: 603401 - La, Thi An (2019)
CHAPTER 1: LITERATURE REVIEW . CHAPTER 2 : RESEARCH METHODOLOGY. CHAPTER 3 : RESEARCH RESULTS. CHAPTER 4 : CONCLUSIONS AND RECOMMENDATIONS